Measuring Sleep in the Intensive Care Unit: A Critical Appraisal of the Use of Subjective Methods. (September 2019) - Jeffs, Emma L.; Darbyshire, Julie L.
Objectives: To collate and appraise the use of subjective measures to assess sleep in the intensive care unit (ICU). Design: A systematic search and critical review of the published literature. Data Sources: Medline, Scopus, and Cumulative Index to Nursing and Allied Health Literature were searched using combinations of the key words "Sleep, " "Critical Care, " "Intensive Care, " and "Sleep Disorders, " and this was complemented by hand searching the most recent systematic reviews on related topics. Study Eligibility Criteria: Papers were limited to non-gray English-language studies of the adult population, published in the last 10 years. Outcome Measures: Primary outcomes were the number and categorization of quantitative studies reporting measures of sleep, the number of participants for each data collection method, and a synthesis of related material to appraise the use of survey tools commonly used for sleep measurement in the ICU. Results: Thirty-eight papers reported quantitative empirical data collection on sleep, 17 of which used a primary method of subjective assessment of sleep by the patient or nurse. Thirteen methods of subjective sleep assessment were identified. Many of these tools lacked validity and reliability testing. Conclusions: Research using questionnaires to assess sleep is commonplace in light of practical barriers to polysomnography or other measures of sleep. A methodologically sound approach to tool development and testing is crucial to gather meaningful data, and this robust approach was lacking in many cases. Further research measuring sleep subjectively in ICU should use the Richards Campbell Sleep Questionnaire, and researchers should maintain a commitment to transparency in describing methods.